(untitled) (Journal of Nepal Geological Society, 2016)
The northward flowing fifth order Kodku Khola confluences with the Manahara River in the southeast of Kathmandu, and has about 16.49 km stretch with 35.67 sq km watershed area. Many large civil engineering structures such as irrigation cannels, bridges, highways and roads are under construction, and are located along and around the river in the urbanizing Kodku Khola valley. Some sections of the river are of high erosion potential due to various reasons. Many human activities together with natural processes have led to bank erosion and channel shifting of the Kodku Khola. Thus, study of the river bank erosion and lateral instability is of great concern as unstable segments of the river may pose threat on civil engineering structures and adjacent agricultural lands. The river bank hazard potential and its variations were assessed in terms of its bank erosion and lateral instability (BELI) hazard indices by considering four parameters namely, bank erosion hazard index (BEHI), near bank stress index (NBSI), lateral instability hazard index (LIHI), and anthropogenic disturbance factors (ADF). For this, thirty nine locations were surveyed throughout the river and assessed the BELI hazard levels. This paper evaluated the BELI hazard levels and channel shifting condition of the Kodku Khola.